Exploring Foreign Language Communication Apprehension among the English Language University Students in the English Language Classroom Setting - Molnar, Draženka; Gabrijela Crnjak (European Journal of Social Science Education and Research, 2020)
Over the past few decades the interest in communication apprehension has increased among researchers and teachers in the field of second/foreign language acquisition (SLA/FLA).The present paper is set between the macro perspective of the social-psychological period – by giving a general view of communication apprehension (CA) – and the situation-specific period – by taking into consideration the immediate educational context.The paper focuses on the phenomenon of communication apprehension among the Croatian university level students in a foreign language classroom setting.In particular, it investigates if there is a difference in the total level of communication apprehension between undergraduate and graduate students of English Language and Literature.Furthermore, it explores whether there is a relationship between different aspects of communication apprehension and the total level of communication apprehension and which background factor is the best predictor of communication apprehension among the students.The first part of the paper brings a theoretical background of the main concepts in this research, whereas the second part of the paper reports on the research itself.Two sets of instruments, questionnaires completed by the students and in-depth interviews conducted among the teachers, were used for the purpose of this study.The results show that the year of study is not a significant predictor of the communication apprehension level which students experience.Among all variables included in the analysis, the only significant predictors of communication apprehension are evaluations.
Keywords: in-class communication apprehension; English as a foreign language; university level; evaluations